Ketamine treatment for depression: A model of care. (December 2021) - Bayes, Adam; Dong, Vanessa; Martin, Donel; Alonzo, Angelo; Kabourakis, Michael; Loo, Colleen
Objective: Ketamine and related compounds are emerging as rapidly acting therapies for treatment-resistant depression. Ketamine differs from standard antidepressants in its speed of action, specific acute and cumulative side effects, risk of dependence and regulatory requirements. However, there is currently little guidance offering translation from research studies into clinical practice. We therefore detail a comprehensive model of care for ketamine treatment of depression. Method: We formulated a set of policies and procedures for a 'compassionate use' ketamine programme that developed out of our clinical research in ketamine. These policies and procedures were formulated into a detailed model of care. Results: The current Australian and New Zealand regulatory frameworks and professional bodies' recommendations regarding ketamine are detailed along with clinical governance and infrastructure considerations. We next describe a four-step model comprising initial assessment, pre-treatment, treatment and post-treatment phases. The model comprises thorough psychiatric and medical assessments examining patient suitability, a rigorous consenting process and structured safety monitoring across an acute treatment course or maintenance therapy. Our ketamine dose-titration method is detailed allowing flexible dosing of patients across a treatment course enabling individualised treatment. Conclusion: The model of care aims to bridge the gap between efficacy studies and clinical care outside of research settings as ketamine and related compounds become increasingly important therapies for treatment-resistant depression.